Leveraging Procore for Improved Collaboration and Communication in Multi-Stakeholder Construction Projects - Rinkesh Gajera (International Journal of Scientific Research in Civil Engineering, 2019)
The multifaceted roles of the contractor, architect, engineer, and project owner are fundamental in effective successful accomplishment of a construction project. Procore is a cloud-based construction management solution that provides the perfect amalgamation of these critical attributes of project management. As outlined in this report, Procore enables improved communication, document sharing, and task streamlining for improved project outcomes. These include Real-time Communication Capability, Centralized Document Management, and Mobile Access. Procore helps work more effectively-not to delay anything-and not to make errors. More importantly, it will discuss how the collection feature of the Procore data can be utilized by project managers for tracking the way work gets done, tasks accomplished, and clear reports that give insight to the performance of the projects. While much benefit exists in Procore, several issues related to implementing existing issues such as training and integration into existing systems add an extra challenge. However, despite these complexities, successful implementation of the product takes place in several projects that make completion faster and communications better. The final report concludes with a summary summarizing that Procore is of significant influence to the use thereof in enhancing collaborative communication in complex construction environments. Consideration has also been given towards future enhancements including AI and VR integration that could further enhance the ability of Procore to optimize project management within the construction industry.
Keywords: Project Management; AI And VR Integration; Mobile Access